A-111 Controlling the impact of HIV-related tuberculosis. (January 2016) - Chaisson, Richard
Abstract : Tuberculosis (TB) remains the leading cause of death in people with HIV infection globally. Reducing the burden of morbidity and mortality caused by TB requires a multipronged strategy aimed at reducing transmission, preventing progression of latent TB to active TB, earlier diagnosis of disease and improved therapeutics. In high-burden settings in Africa, the force of TB infection is high and results in continual exposure and re-exposure to infection. Reducing the force of infection requires improved case detection and prompt, effective treatment. Prevention of progression of latent infection is achievable with the combination of antiretroviral therapy and TB preventive therapy. The recent START study demonstrated the efficacy of ART in reducing TB incidence, and the TEMPRANO study confirmed the independent and additive contribution of isoniazid preventive therapy to ART. Prolonged courses of preventive therapy are probably required in high-burden settings, though more sterilizing regimens using rifamycins may be effective. Reducing mortality from TB requires early detection and treatment, as well as improved regimens for multidrug resistant TB. Preventive therapy for HIV-infected contacts of MDR TB cases is an urgent unmet need.